Gravo‐aeroelastic scaling of a 13‐MW downwind rotor for 20% scale blades. Issue 3 (29th September 2020) - Kaminski, Meghan; Noyes, Carlos; Loth, Eric; Damiani, Rick; Hughes, Scott; Bay, Christopher; Chetan, Mayank; Griffith, D. Todd; Johnson, Kathryn; Martin, Dana
Abstract: A 105‐m, 13‐MW two‐bladed downwind Segmented Ultralight Morphing Rotor (SUMR‐13) blade was gravo‐aeroelastically scaled by 20% to a 20.87‐m‐long demonstrator blade and confirmed through structural ground testing. The subscale model was achieved through geometric scaling and by aeroelastic scaling principles based on operational flapwise deflections combined with rotational and structural frequencies while retaining the turbine tip‐speed ratio. In particular, the subscale demonstrator was designed to replicate, as closely as possible, the nondimensional geometry, the ratio of centrifugal to gravitational moments, the tip‐speed ratio, and the nondimensional rotation rate. The intent for this demonstrator was to achieve the same nondimensional flapwise blade deflections and dynamics of the full‐scale 13‐MW rotor. The manufactured SUMR‐D blade resulted in less than half of the mass of the conventional two‐bladed Controls Advanced Research Turbine (CART2) rotor blade based on scaling and a lower power rating, though with some differences in mass and stiffness from the ideal scaled‐down design to meet safety requirements at the test site. To achieve proper scaling, operational pitch control set points were altered to account for the differences by evaluating simulated operation of both the SUMR‐13 and SUMR‐D rotors. Structural testing of the SUMR‐D blade investigated the response to well‐defined flapwise loads and indicated that the subscale blade had the appropriate elastic properties needed for both scaling and for safe operational field testing.